2018
DOI: 10.1002/fsn3.670
|View full text |Cite
|
Sign up to set email alerts
|

Proximate composition, functional, and pasting properties of wheat and groundnut protein concentrate flour blends

Abstract: This study investigated the effect of groundnut protein concentrate inclusion on the quality of wheat flour. Wheat and groundnut concentrate flours were blended (%, w/w) at ratios 100:0, 95:5, 90:10, 85:15, and 80:20, with 100% wheat flour serving as the control sample. Subsequently, proximate composition, functional, and pasting properties of blends were determined using established methods. Protein content of the concentrate was 72.80%. Significant (p < .05) increase in protein content of the flour blends wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
65
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(119 citation statements)
references
References 29 publications
26
65
2
Order By: Relevance
“…The composite flour had higher pasting temperature than mocaf. These observations are similar to those reported by Ocheme et al (2018), who showed that higher pasting temperatures with increasing groundnut protein concentrate (GPC) reflect higher water absorption capacity of the blends with higher GPC contents.…”
Section: Pasting Propertiessupporting
confidence: 91%
“…The composite flour had higher pasting temperature than mocaf. These observations are similar to those reported by Ocheme et al (2018), who showed that higher pasting temperatures with increasing groundnut protein concentrate (GPC) reflect higher water absorption capacity of the blends with higher GPC contents.…”
Section: Pasting Propertiessupporting
confidence: 91%
“…The moisture content of the samples ranged from 13.81 to 14.20% with 100% wheat flour having the highest value. The lower values of LRF-WF blends is advantageous because it will reduce the proliferation of spoilage organisms, especially mold, thus, improving the shelf stability of the product (Ocheme et al, 2018). The protein content of LRF-WF blends increased from 10.80 to 11.70%, and ash content increased from 0.62 to 1.07%, while fat content of flour blends was not significantly different (P ≤ 0.05).…”
Section: Physicochemical Propertiesmentioning
confidence: 97%
“…Carbohydrate content of flour blends ranged from 71.83 to 73.02%. Generally, vegetable flour has been incorporated in numerous food products for better nutritional profile and functionality than products solely made from wheat flour (Ocheme et al, 2018). Furthermore, the addition of LRF reduced the dry gluten content and gluten index (GI) of flour blends.…”
Section: Physicochemical Propertiesmentioning
confidence: 99%
“…This result could be due to low moisture content of the watermelon rind powder used in the blends as shown by Table 2. This is advantageous because reduction in moisture content will reduce the proliferation of spoilage microorganism especially mold, thus improving shelf stability of the product [22]. [24].…”
Section: Effect Of Watermelon Rind Addition On the Proximate Compositmentioning
confidence: 99%